Comparative Study of REACT Learning with Problem-Based Learning on Concepts and Problem-solving Skills in High School - Praitno Simarmata (JMEA : Journal of Mathematics Education and Application, 2022)
Preliminary studies show that students' problem-solving and creative thinking skills are still low. The application of a realistic mathematics learning model with Jigsaw type cooperative setting is one way to improve it. The focus of this research is to see how a realistic mathematics learning model with a Jigsaw-style cooperative setting affects students' problem-solving and creative thinking skills. A test of problem-solving skills and a test of creative thinking skills are included in the study instrument. The two-way Manova test was employed for data analysis. (1) A realistic mathematics learning model with Jigsaw type cooperative environment has an effect on students' problem-solving abilities with Fhit Ftable of 21,957 3,13, according to the findings. (2) A realistic mathematics learning model with a Jigsaw cooperative type setting has an effect on students' creative thinking ability when Fhit Ftable is 9.206 3.13 (3) Students with Fhit Ftable ie 16.126 3.13 have an influence of a realistic mathematics learning model with Jigsaw type cooperative setting on problem-solving ability and creative thinking capacity. As a result, the realistic mathematics learning approach can help pupils develop their problem-solving and creative-thinking skills.